The Rapid Assessment of Competency in Echocardiography Scale: Validation of a Tool for Point‐of‐Care Ultrasound. (31st May 2016) - Millington, Scott J.; Arntfield, Robert T.; Hewak, Michael; Hamstra, Stanley J.; Beaulieu, Yanick; Hibbert, Benjamin; Koenig, Seth; Kory, Pierre; Mayo, Paul; Schoenherr, Jordan R.
Abstract : Objectives: Increased use of point‐of‐care ultrasound (US) requires the development of assessment tools that measure the competency of learners. In this study, we developed and tested a tool to assess the quality of point‐of‐care cardiac US studies performed by novices. Methods: In phase 1, the Rapid Assessment of Competency in Echocardiography (RACE) scale was developed on the basis of structured interviews with subject matter experts; the tool was then piloted on a small series of US studies in phase 2. In phase 3, the tool was applied to a sample of 154 point‐of‐care US studies performed by 12 learners; each study was independently rated by 2 experts, with quantitative analysis subsequently performed. Results: Evidence of the content validity of the RACE scale was supported by a consensus exercise, wherein experts agreed on the assessment dimensions and specific items that made up the RACE scale. The tool showed good inter‐rater reliability. An analysis of inter‐item correlations provided support for the internal structure of the scale, and the tool was able to discriminate between learners early in their point‐of‐care US learning and those who were more advanced in their training. Conclusions: The RACE scale provides a straightforward means to assess learner performance with minimal requirements for evaluator training. Our results support the conclusion that the tool is an effective means of making valid judgments regarding competency in point‐of‐care cardiac US.